Dosimetric Comparison of IMRT Versus 3DCRT for Post-mastectomy Chest Wall Irradiation: An Analytical Observational Study - Tali, Tavseef Ahmad; Amin, Fiza; Ahmad, Javaid; Ahmad Khan, Aijaz (Asian Pacific Journal of Cancer Care, 2022)
Purpose: To compare the dose distribution of three-dimensional conformal radiation therapy (3DCRT) with intensity-modulated radiation therapy (IMRT) for post-mastectomy radiotherapy (PMRT) to left chest wall. Materials and Methods: 30 post-MRM female breast cancer patients with histologically confirmed infiltrating ductal carcinoma of unilateral left breast without evidence of distant metastasis or second malignancy were found eligible during January 2017 to December 2021. All patients received 45 Gy in 20 fractions. Planning target volume (PTV) parameters -D2, D98, Dmean, V95, and V107—homogeneity index (HI), and conformity index (CI) were compared. The mean doses of lung and heart, percentage volume of ipsilateral lung receiving 5 Gy (V5), 20 Gy (V20), and 49 Gy (V49) and that of heart receiving 5 Gy (V5), 25 Gy (V25), and 42 Gy (V42) were extracted from dose-volume histograms and compared. Results: PTV parameters were comparable between the two groups. CI was significantly improved with IMRT (1.118 vs. 1.224, p < 0.04) but HI was similar (0.0951 vs. 0.0962, p = 0.125) compared to 3DCRT. IMRT in comparison to 3DCRT significantly reduced the high-dose volumes of lung (V20, 24.52% vs. 29.62%; V49, 3.56% vs. 6.42%; p < 0.001) and heart (V25, 5.89% vs. 8.24%; V42, 1.64% vs. 6.12%; p < 0.001); mean dose of lung and heart (10.21 vs. 11.96 Gy and 3.86 vs. 7.42 Gy, respectively; p < 0.001). Conclusions: For left sided breast cancer, IMRT significantly improves the conformity of plan and reduce the mean dose and high-dose volumes of ipsilateral lung and heart compared to 3DCRT, but 3DCRT is superior in terms of low-dose volume.